Modified TiO2 / g-C3N4 photocatalyst and preparation method thereof

By loading the nano-hydrocarbon white sludge into the surface or pores of TiO2/g-C3N4, the problem of low specific surface area and catalytic activity of existing TiO2/g-C3N4 photocatalysts is solved, the specific surface area is improved and the preparation cost is reduced, and the photocatalytic performance is improved.

CN119702036APending Publication Date: 2025-03-28CHINA SHENHUA ENERGY CO LTD HARWUSU OPEN-PIT COAL MINE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411706906.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing TiO2/g-C3N4 photocatalysts have low specific surface area and catalytic activity, complex preparation process and high cost.

Method used

By loading the nano-hydrocarbon white sludge into the surface or pores of TiO2/g-C3N4, the specific surface area of ​​the modified TiO2/g-C3N4 photocatalyst is increased to 520-605 m2/g, and the preparation method is simplified and the cost is reduced.

Benefits of technology

The photocatalytic performance of the modified TiO2/g-C3N4 photocatalyst is improved, its response range to visible light is increased, and the preparation cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702036A_ABST
    Figure CN119702036A_ABST
Patent Text Reader

Abstract

The invention provides a modified TiO2 / g-C3N4 photocatalyst and a preparation method of the modified TiO2 / g-C3N4 photocatalyst. The modified TiO2 / g-C3N4 photocatalyst is prepared from TiO2 / g-C3N4 and nano hydrocarbon white mud loaded on the surface or in pores of TiO2 / g-C3N4, and the specific surface area of the modified TiO2 / g-C3N4 photocatalyst is 520 to 605 m < 2 > / g. The nano hydrocarbon white mud is loaded on the surface of TiO2 / g-C3N4 or in pores to modify the surface of TiO2, so that the specific surface area of the modified TiO2 / g-C3N4 photocatalyst is within the range, and the overall photocatalytic performance of the modified TiO2 / g-C3N4 photocatalyst is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a modified TiO 2 / gC 3 N 4 Photocatalyst and method for preparing the same. Background Art

[0002] At present, the world's energy shortage and environmental pollution are major problems facing mankind. Photocatalytic technology can be used to effectively treat inorganic and organic pollutants, produce hydrogen and oxygen by hydrolysis, reduce carbon dioxide and organic synthesis. This technology is not only green and environmentally friendly, but also has the advantages of low energy consumption, mild reaction conditions, safety and effectiveness. Therefore, photocatalytic technology has gradually become a hot topic.

[0003] Although TiO 2 The band gap width of TiO is about 3.2eV, but only ultraviolet light with a shorter wavelength can catalyze its activity, and ultraviolet light only accounts for 4% of sunlight, which limits the activity of TiO 2 Widely used in the field of photocatalysis. In order to broaden the spectral absorption range and improve the photocatalytic performance, TiO 2 A lot of surface modification research has been carried out. Carbon nitride is a polymer material with excellent thermal stability. It is a yellow powder and is non-toxic and pollution-free. It also has a unique two-dimensional planar conjugated structure and ultimately exhibits excellent physical and chemical properties. 3 N 4 The bandgap width of gC is about 2.7 eV, which makes 3 N 4 Can be excited by visible light and react with TiO 2 The coupling forms a heterogeneous interface, which significantly improves the response range of the catalyst to visible light, and also promotes the separation of photogenerated electrons and holes in the material, thereby inhibiting the recombination of electrons and holes, and thus improving the photocatalytic performance. 2 / gC 3 N 4 The catalyst process is complex and costly, and it is difficult to prepare a multi-level structure TiO with a high specific surface area. 2 / gC 3 N 4 catalyst. Summary of the invention

[0004] The main purpose of the present invention is to provide a modified TiO 2 / gC 3 N 4 Photocatalyst and preparation method thereof to solve the problem of TiO 2 / gC 3 N 4The photocatalyst has the problems of low specific surface area and catalytic activity, complex preparation process and high cost.

[0005] In order to achieve the above object, according to one aspect of the present invention, a modified TiO 2 / gC 3 N 4 Photocatalyst, the modified TiO 2 / gC 3 N 4 Photocatalysts include TiO 2 / gC 3 N 4 and loaded on TiO 2 / gC 3 N 4 The surface or pores of the nanocarbon white mud, wherein the modified TiO 2 / gC 3 N 4 The specific surface area of ​​the photocatalyst is 520~605m 2 / g.

[0006] Furthermore, the TiO 2 / gC 3 N 4 The mass ratio of the nano-carbon white mud is 1 to 9:1.

[0007] Furthermore, the modified TiO 2 / gC 3 N 4 The average particle size of the photocatalyst is 20 to 30 μm, and / or the porosity of the nanocarbon white mud is 65 to 85%, and / or the average particle size of the nanocarbon white mud is 2.2 to 13.5 μm, and / or the specific surface area of ​​the nanocarbon white mud is 70 to 90 m 2 / g.

[0008] According to one aspect of the present invention, there is provided a modified TiO 2 / gC 3 N 4 The preparation method of the photocatalyst comprises: step S1, first mixing raw materials including a titanium source, urea and a solvent A to obtain a first mixture; step S2, sequentially performing a second mixing and standing of raw materials including the first mixture, water and an acidic solution to obtain a sol; step S3, sequentially performing a first drying and a first calcination of the sol to obtain TiO 2 / gC 3 N 4 Precursor; Step S4, comprising TiO 2 / gC 3 N 4The raw materials of the precursor, the nanocarbon white mud and the solvent B are subjected to ultrasonic dispersion, first stirring, second drying and second calcination in sequence to obtain modified TiO 2 / gC 3 N 4 Photocatalyst.

[0009] Furthermore, the above step S1 includes: mixing the titanium source and solvent A to obtain a mixed solution; mixing the mixed solution with urea to obtain a first mixture; and / or the titanium source is tetrabutyl titanate, and / or the volume ratio of the titanium source and solvent A is 1:2 to 3; the mass ratio of urea to tetrabutyl titanate is 0.23 to 0.46 g / mL; and / or solvent A is anhydrous ethanol and / or methanol.

[0010] Furthermore, in the above step S1, a second stirring is performed during the first mixing process, the second stirring time is 10 to 30 minutes, and / or the second stirring speed is 30 to 60 rpm, and / or the second stirring temperature is 20 to 30°C.

[0011] Furthermore, in the above step S2, the volume ratio of the acidic solution to water is 1:10 to 1:14; and / or the acidic solution is selected from hydrochloric acid and / or acetic acid with a molar concentration of 10 to 12 mol / L; and / or the water is deionized water; and / or a third stirring is performed during the second mixing process, and the third stirring time is 30 to 60 min, and / or the third stirring speed is 30 to 60 rpm, and / or the third stirring temperature is 20 to 30° C.; and / or the standing time is 12 to 24 h.

[0012] Furthermore, in the above step S3, the first drying temperature is 80-95°C, and / or the first drying time is 4-8h; and / or the first calcination is performed at a heating rate of 5-8°C / min and then cooled to room temperature, and / or the first calcination temperature is 500-600°C, and / or the first calcination time is 2-5h.

[0013] Furthermore, in the above step S4, TiO 2 / gC 3 N 4 The mass ratio of the precursor to the nanocarbon white mud is 1.5 to 3.96:1; and / or, TiO 2 / gC 3 N 4 The mass ratio of the precursor to the volume ratio of the solvent B is 0.028-0.084 g / mL; and / or, the solvent B is anhydrous ethanol and / or methanol; and / or, the nano-carbon hydrogen white mud is obtained by acid dissolution of nano-carbon hydrogen fly ash.

[0014] Further, in the above step S4, the time of ultrasonic dispersion is 30 to 60 minutes; and / or, the frequency of ultrasonic dispersion is 20 to 50 kHz; and / or, the time of the first stirring is 4 to 6 hours, and / or, the rotation speed of the first stirring is 40 to 80 rpm, and / or, the temperature of the first stirring is 20 to 30°C; and / or, the temperature of the second drying is 80 to 95°C, and / or, the time of the second drying is 2 to 6 hours; and / or, the second calcination is carried out at a heating rate of 5 to 8°C / min and then cooled to room temperature, and / or, the temperature of the second calcination is 350 to 450°C, and / or, the time of the second calcination is 2 to 4 hours.

[0015] Using the technical solution of the present invention, the nanocarbon white mud is the solid waste residue after the nanocarbon fly ash is dissolved by acid, which is in powder form and has excellent characteristics such as small particle size, high porosity, large specific surface area, and high activity. 2 / gC 3 N 4 The surface or pores of TiO 2 The surface of the modified TiO 2 / gC 3 N 4 The specific surface area of ​​the photocatalyst is within the above range, thereby increasing the modified TiO 2 / gC 3 N 4 The photocatalytic performance of the photocatalyst as a whole. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0017] Figure 1 The TiO in Example 2 of the present application is shown 2 / gC 3 N 4 SEM image of the precursor;

[0018] Figure 2 shows a SEM image of the photocatalyst in Example 2 of the present application;

[0019] Figure 3 The graph shows the degradation rate of methyl orange wastewater degraded by photocatalysts of different concentrations in Example 2 of the present application. DETAILED DESCRIPTION

[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0021] As analyzed in the background technology of this application, the prior art has the problems of low specific surface area and catalytic activity of photocatalysts, complex preparation process and high cost. In order to solve the above problems, this application provides a modified TiO 2 / gC 3 N 4 Photocatalyst and method for preparing the same.

[0022] In a typical embodiment of the present application, a modified TiO 2 / gC 3 N 4 Photocatalyst, the modified TiO 2 / gC 3 N 4 Photocatalysts include TiO 2 / gC 3 N 4 and loaded on TiO 2 / gC 3 N 4 The surface or pores of the nanocarbon white mud, wherein the modified TiO 2 / gC 3 N 4 The specific surface area of ​​the photocatalyst is 520~605m 2 / g.

[0023] Nanocarbon white mud is the solid waste residue after the acid dissolution of nanocarbon fly ash. It is in powder form and has excellent properties such as small particle size, high porosity, large specific surface area and high activity. 2 / gC 3 N 4 The surface or pores of TiO 2 The surface of the modified TiO 2 / gC 3 N 4 The specific surface area of ​​the photocatalyst is within the above range, thereby increasing the modified TiO 2 / gC 3 N 4 The photocatalytic performance of the photocatalyst as a whole.

[0024] In one embodiment of the present application, the TiO 2 / gC 3 N 4 The mass ratio of the nano-carbon white mud is 1 to 9:1.

[0025] Preferred TiO 2 / gC 3 N 4The mass ratio of TiO2 to nano-carbon white mud is within the above range, which is more helpful to improve the 2 / gC 3 N 4 Photocatalytic performance of photocatalysts.

[0026] In one embodiment of the present application, the modified TiO 2 / gC 3 N 4 The average particle size of the photocatalyst is 20 to 30 μm, and / or the porosity of the nanocarbon white mud is 65 to 85%, and / or the average particle size of the nanocarbon white mud is 2.2 to 13.5 μm, and / or the specific surface area of ​​the nanocarbon white mud is 70 to 90 m 2 / g.

[0027] Nanocarbon white mud with the above average particle size can better 2 / gC 3 N 4 Matching, thus TiO 2 / gC 3 N 4 The preferred nanocarbon white mud with the above porosity and specific surface area can more fully modify TiO 2 / gC 3 N 4 The pore structure of modified TiO 2 / gC 3 N 4 The specific surface area of ​​the photocatalyst is increased, thereby improving the modified TiO 2 / gC 3 N 4 Photocatalytic performance of photocatalysts.

[0028] In another typical embodiment of the present application, a modified TiO 2 / gC 3 N 4 The preparation method of the photocatalyst comprises: step S1, first mixing raw materials including a titanium source, urea and a solvent A to obtain a first mixture; step S2, sequentially performing a second mixing and standing of raw materials including the first mixture, water and an acidic solution to obtain a sol; step S3, sequentially performing a first drying and a first calcination of the sol to obtain TiO 2 / gC 3 N 4 Precursor; Step S4, comprising TiO 2 / gC 3 N 4The raw materials of the precursor, the nanocarbon white mud and the solvent B are subjected to ultrasonic dispersion, first stirring, second drying and second calcination in sequence to obtain modified TiO 2 / gC 3 N 4 Photocatalyst.

[0029] Nanocarbon white mud is the solid waste residue after the acid dissolution of nanocarbon fly ash. It is in powder form and has excellent properties such as small particle size, high porosity, large specific surface area and high activity. 2 / gC 3 N 4 The surface or pores of TiO 2 The surface of the modified TiO 2 / gC 3 N 4 The specific surface area of ​​the photocatalyst is within the above range, thereby increasing the modified TiO 2 / gC 3 N 4 The photocatalytic performance of the photocatalyst as a whole. And the above preparation method of the present application is simple, the conditions are mild and controllable, and the cost is low.

[0030] Among them, nano-carbon fly ash is produced after high-temperature calcination of nano-carbon fuel, and nano-carbon white mud is the solid waste residue after acid dissolution of nano-carbon fly ash.

[0031] In order to improve the synergistic effect of titanium source, solvent A and urea, the prepared TiO 2 / gC 3 N 4 The photocatalytic performance is better. In one embodiment of the present application, the above-mentioned step S1 preferably includes: mixing the titanium source and solvent A to obtain a mixed liquid; mixing the mixed liquid with urea to obtain a first mixture; and / or the titanium source is tetrabutyl titanate, and / or the volume ratio of the titanium source to solvent A is 1:2-3; the mass ratio of urea to tetrabutyl titanate is 0.23-0.46 g / mL; and / or solvent A is anhydrous ethanol and / or methanol.

[0032] In one embodiment of the present application, in the above step S1, a second stirring is performed during the first mixing process, the second stirring time is 10 to 30 minutes, and / or the second stirring speed is 30 to 60 rpm, and / or the second stirring temperature is 20 to 30°C.

[0033] The above preferred conditions are helpful to improve the uniformity of the first mixing.

[0034] In one embodiment of the present application, in the above step S2, the volume ratio of the acidic solution to water is 1:10 to 1:14; and / or the acidic solution is selected from hydrochloric acid and / or acetic acid with a molar concentration of 10 to 12 mol / L; and / or the water is deionized water; and / or a third stirring is performed during the second mixing process, and the time of the third stirring is 30 to 60 min, and / or the rotation speed of the third stirring is 30 to 60 rpm, and / or the temperature of the third stirring is 20 to 30°C; and / or the standing time is 12 to 24 h.

[0035] The above preferred conditions are beneficial to improving the efficiency and effect of the solation reaction.

[0036] In one embodiment of the present application, in the above step S3, the temperature of the first drying is 80-95°C, and / or the time of the first drying is 4-8h; and / or the first calcination is performed at a heating rate of 5-8°C / min and then cooled to room temperature, and / or the temperature of the first calcination is 500-600°C, and / or the time of the first calcination is 2-5h.

[0037] The preferred conditions for the first drying above are helpful to improve the efficiency and effect of the first drying. The preferred conditions for the first calcining above are helpful to improve the efficiency and effect of the first calcining.

[0038] In one embodiment of the present application, in the above step S4, TiO 2 / gC 3 N 4 The mass ratio of the precursor to the nanocarbon white mud is 1.5 to 3.96:1; and / or, TiO 2 / gC 3 N 4 The mass ratio of the precursor to the volume ratio of the solvent B is 0.028-0.084 g / mL; and / or, the solvent B is anhydrous ethanol and / or methanol; and / or, the nano-carbon hydrogen white mud is obtained by acid dissolution of nano-carbon hydrogen fly ash.

[0039] Preferred TiO 2 / gC 3 N 4 Controlling the mass ratio of the precursor and the nanocarbon white mud helps to obtain modified TiO with an appropriate nanocarbon white mud loading. 2 / gC 3 N 4 Photocatalyst. Preferably TiO 2 / gC 3 N 4 The mass of the precursor and the volume ratio of solvent B as well as the type of solvent B are helpful to improve the TiO 2 / gC 3 N 4Dispersion uniformity of precursor and nanocarbon white mud in solvent B.

[0040] To further improve TiO 2 / gC 3 N 4 Precursor and nano-carbon white mud dispersion uniformity in solvent B, in one embodiment of the present application, preferably in the above step S4, the ultrasonic dispersion time is 30 to 60 minutes; and / or, the ultrasonic dispersion frequency is 20 to 50kHz; and / or, the first stirring time is 4 to 6 hours, and / or, the first stirring speed is 40 to 80rpm, and / or, the first stirring temperature is 20 to 30°C. And / or, the second drying temperature is 80 to 95°C, and / or, the second drying time is 2 to 6 hours; and / or, the second roasting is carried out at a heating rate of 5 to 8°C / min and then cooled to room temperature, and / or, the second roasting temperature is 350 to 450°C, and / or, the second roasting time is 2 to 4 hours.

[0041] The above preferred second drying conditions are helpful to improve the efficiency and effect of the second drying. The above preferred second roasting conditions are helpful to improve the efficiency and effect of the second roasting.

[0042] The beneficial effects of the present application will be further illustrated below in conjunction with embodiments.

[0043] Example 1

[0044] 25 mL of tetrabutyl titanate was slowly added to 75 mL of stirred anhydrous ethanol; 8.8 g of urea was then added to the mixture and continued to stir at room temperature for 10 minutes; 25 mL of deionized water was slowly added to the mixed solution, and a few drops of HCl were immediately added, and stirring was continued for 30 minutes; the mixture was allowed to stand for 18 hours to form a sol-gel; the mixture was dried in a forced air dryer at 80°C for 5 hours and ground; the product was transferred to a covered crucible and baked in a muffle furnace at 500°C and 5°C / min for 3 hours; after cooling to room temperature, TiO 2 / gC 3 N 4 Precursor.

[0045] 2.1 g TiO 2 / gC 3 N 4 The precursor was dissolved in 50 mL of anhydrous ethanol with 0.53 g of nanocarbon white mud; after ultrasonication for 30 minutes, the mixed solution was stirred by magnetic force for more than 4 hours; then dried to a solid state and transferred to a crucible, and placed in a roasting furnace for roasting at 450 ° C at a rate of 5 ° C / min, and the temperature was maintained for 3 hours to obtain TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0046] Take 100 mL of methyl orange solution with a concentration of 20 mg / L and a pH of 6, add 0.50 g of the prepared TiO 2 / gC 3 N 4 / white mud photocatalyst, constant temperature oscillation for 1h, after adsorption reaches equilibrium, open visible light source irradiation, time to 150min, photocatalytic degradation experiment. After the experiment, take out the solution, filter it, and use ultraviolet spectrophotometer to measure the concentration of methyl orange in the supernatant. According to R=C 0 -C e / C 0 , calculate the removal rate, where R is the removal rate (%), C 0 is the initial concentration of methyl orange in the solution (mg / L), C e is the concentration of methyl orange in the solution after the photocatalytic reaction (mg / L). The experimental results are shown in Table 1.

[0047] Example 2

[0048] 25 mL of tetrabutyl titanate was slowly added to 50 mL of stirred anhydrous ethanol; 5.75 g of urea was then added to the mixture and continued to stir at room temperature for 10 minutes; 25 mL of deionized water was slowly added to the mixed solution, and a few drops of HCl were immediately added, and stirring was continued for 30 minutes; the mixture was allowed to stand for 20 hours to form a sol-gel; the mixture was dried in a forced air dryer at 80°C for 6 hours and ground; the product was transferred to a covered crucible and baked in a muffle furnace at 550°C and 5°C / min for 4 hours; after cooling to room temperature, TiO 2 / gC 3 N 4 The SEM image of the precursor is as follows Figure 1 shown.

[0049] 2.1 g TiO 2 / gC 3 N 4 The precursor was dissolved in 50 ml of anhydrous ethanol with 0.9 g of nanocarbon white mud; after ultrasonication for 30 minutes, the mixed solution was stirred by magnetic force for 4 hours; then dried to a solid state and transferred to a crucible, and placed in a roasting furnace for roasting at 400 ° C, at a rate of 5 ° C / min, and the temperature was maintained for 2 hours to obtain TiO 2 / gC 3 N 4 / white mud photocatalyst, its SEM image is as follows Figure 2 shown.

[0050] Take 100 mL of methyl orange solution with a concentration of 20 mg / L and a pH of 6, add 0.06 g, 0.13 g, 0.25 g, 0.50 g, and 0.60 g of the prepared TiO 2 / gC 3 N 4 / white mud photocatalyst, constant temperature oscillation for 1h, after adsorption reaches equilibrium, open visible light source irradiation, time to 150min, photocatalytic degradation experiment. From the beginning to the end of the experiment, take out the solution at a certain interval, filter it, and use ultraviolet spectrophotometer to measure the concentration of methyl orange in the supernatant. According to R=C 0 -C e / C 0 , calculate the removal rate, where R is the removal rate (%), C 0 is the initial concentration of methyl orange in the solution (mg / L), C e is the concentration of methyl orange in the solution after the photocatalytic reaction (mg / L). The experimental results are shown in Table 1. The TiO 2 / gC 3 N 4 The degradation rate of methyl orange wastewater by white mud photocatalyst is shown in Figure 3 shown.

[0051] Example 3

[0052] 25 mL of tetrabutyl titanate was slowly added to 50 mL of stirred anhydrous ethanol; 11.5 g of urea was then added to the mixture and stirred for 10 minutes at room temperature; 30 mL of deionized water was slowly added to the mixed solution, and a few drops of HCl were immediately added and stirred for 30 minutes; the mixture was allowed to stand for 15 hours to form a sol-gel; the mixture was dried in a forced air dryer at 80°C for 4 hours and ground; the product was transferred to a covered crucible and baked in a muffle furnace at 580°C and 5°C / min for 5 hours; after cooling to room temperature, TiO 2 / gC 3 N 4 Precursor.

[0053] 2.1 g TiO 2 / gC 3 N 4 The precursor was dissolved in 50 ml of anhydrous ethanol with 1.4 g of nanocarbon white mud; after ultrasonication for 30 minutes, the mixed solution was stirred by magnetic force for 4 hours; then dried to a solid state and transferred to a crucible, and placed in a roasting furnace for roasting at 380 ° C at a rate of 5 ° C / min, and the temperature was maintained for 4 hours to obtain TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0054] Take 100 mL of methyl orange solution with a concentration of 20 mg / L and a pH of 6, add 0.50 g of the prepared TiO 2 / gC 3 N 4 / white mud photocatalyst, constant temperature oscillation for 1h, after adsorption reaches equilibrium, open visible light source irradiation, time to 150min, photocatalytic degradation experiment. After the experiment, take out the solution, filter it, and use ultraviolet spectrophotometer to measure the concentration of methyl orange in the supernatant. According to R=C 0 -C e / C 0 , calculate the removal rate, where R is the removal rate (%), C 0 is the initial concentration of methyl orange in the solution (mg / L), C e is the concentration of methyl orange in the solution after the photocatalytic reaction (mg / L). The experimental results are shown in Table 1.

[0055] Example 4

[0056] The difference from Example 2 is that TiO 2 / gC 3 N 4 The mass ratio of precursor to nanocarbon white mud is 1.5:1, and finally TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0057] Example 5

[0058] The difference from Example 2 is that TiO 2 / gC 3 N 4 The mass ratio of precursor to nanocarbon white mud is 3.96:1, and finally TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0059] Example 6

[0060] The difference from Example 2 is that TiO 2 / gC 3 N 4 The mass ratio of the precursor to the nanocarbon white mud is 1:1, and the final TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0061] Example 7

[0062] 25 mL of tetrabutyl titanate was slowly added to 75 mL of stirred anhydrous ethanol; 11.5 g of urea was then added to the mixture and stirred for 10 minutes at room temperature; 25 mL of deionized water was slowly added to the mixed solution, and a few drops of HCl were immediately added, and stirring was continued for 40 minutes; the mixture was allowed to stand for 12 hours to form a sol-gel; the mixture was dried in a forced air dryer at 80°C for 7 hours and ground; the product was transferred to a covered crucible and baked in a muffle furnace at 500°C and 5°C / min for 4 hours; after cooling to room temperature, TiO 2 / gC 3 N 4 Precursor.

[0063] 2.1 g of TiO 2 / gC 3 N 4 The precursor was dissolved in 25 ml of anhydrous ethanol with 1.8 g of nanocarbon white mud; after ultrasonication for 30 minutes, the mixed solution was stirred by magnetic force for 5 hours; then dried to a solid state and transferred to a crucible, and placed in a roasting furnace for roasting at 400 ° C at a rate of 5 ° C / min, and the temperature was maintained for 2 hours to obtain TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0064] Example 8

[0065] 25 mL of tetrabutyl titanate was slowly added to 25 mL of stirred anhydrous ethanol; 8.8 g of urea was then added to the mixture and continued to stir at room temperature for 20 minutes; 50 mL of deionized water was slowly added to the mixed solution, and a few drops of HCl were immediately added, and stirring was continued for 30 minutes; the mixture was allowed to stand for 16 hours to form a sol-gel; the mixture was dried in a 90°C forced air dryer for 6 hours and ground; the product was transferred to a covered crucible and baked in a muffle furnace at 550°C and 6°C / min for 3 hours; after cooling to room temperature, TiO 2 / gC 3 N 4 Precursor.

[0066] 2.1 g TiO 2 / gC 3 N 4 The precursor was dissolved in 75 ml of anhydrous ethanol with 1.4 g of nanocarbon white mud; after ultrasonication for 40 minutes, the mixed solution was stirred by magnetic force for 6 hours; then dried to a solid state and transferred to a crucible, and placed in a calcining furnace for calcination at 450 °C at a rate of 7 °C / min for 3 hours to obtain TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0067] Example 9

[0068] 25 mL of tetrabutyl titanate was slowly added to 50 mL of stirred anhydrous ethanol; 6.5 g of urea was then added to the mixture and continued to stir at room temperature for 10 minutes; 25 mL of deionized water was slowly added to the mixed solution, and a few drops of HCl were immediately added, and stirring was continued for 60 minutes; the mixture was allowed to stand for 24 hours to form a sol-gel; the mixture was dried in a forced air dryer at 85°C for 7 hours and ground; the product was transferred to a covered crucible and baked in a muffle furnace at 600°C and 6°C / min for 4 hours; after cooling to room temperature, TiO 2 / gC 3 N 4 Precursor.

[0069] 2.1 g TiO 2 / gC 3 N 4 The precursor was dissolved in 50 ml of anhydrous ethanol with 0.7 g of nanocarbon white mud; after ultrasonication for 30 minutes, the mixed solution was stirred magnetically for 4 hours; then dried to a solid state and transferred to a crucible, and placed in a roasting furnace for roasting at 350 ° C at a rate of 5 ° C / min, and the temperature was maintained for 4 hours to obtain TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0070] Comparative Example 1

[0071] The difference from Example 6 is that fly ash is used instead of nano-carbon white mud to finally obtain TiO 2 / gC 3 N 4 / White mud photocatalyst.

[0072] The TiO 2 / gC 3 N 4 The removal efficiency of methyl orange by the photocatalyst of / white mud is shown in Table 1.

[0073] Table 1

[0074]

[0075]

[0076] As can be seen from Table 1, the photocatalytic experiments were conducted with different addition amounts of the photocatalyst prepared in Example 2. Figure 3It can be seen that with the increase of reaction time, the removal rate of different addition amounts shows an increasing trend. When the addition amount is 0.5 g / mL, the removal rate of methyl orange is the best, which can reach 98.0%, and the methyl orange removal effect is the best. 2 / gC 3 N 4 Precursors and TiO 2 / gC 3 N 4 / white mud photocatalysts were tested and analyzed by SEM. Figure 1 , 2 As shown, the particles are about a few nanometers, and the small particles are tightly packed to form a large number of pores and holes, which will lead to a larger porosity and specific surface area of ​​the catalyst, thereby increasing its adsorption performance. 3 N 4 With TiO 2 The tight heterojunction structure formed between them can effectively promote the transfer of photogenerated carriers, inhibit the recombination of electrons and holes, and thus improve the photon quantum efficiency and degradation rate.

[0077] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0078] Nanocarbon white mud is the solid waste residue after the acid dissolution of nanocarbon fly ash. It is in powder form and has excellent properties such as small particle size, high porosity, large specific surface area and high activity. 2 / gC 3 N 4 The surface or pores of TiO 2 The surface of the modified TiO 2 / gC 3 N 4 The specific surface area of ​​the photocatalyst is within the above range, thereby increasing the modified TiO 2 / gC 3 N 4 The photocatalytic performance of the photocatalyst as a whole.

[0079] The above are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A modified TiO2 / g-C3N4 photocatalyst, characterized in that: The modified TiO2 / g-C3N4 photocatalyst comprises TiO2 / g-C3N4 and nanocarbon white mud supported on the surface or in the pores of the TiO2 / g-C3N4, wherein the specific surface area of ​​the modified TiO2 / g-C3N4 photocatalyst is 520-605 m 2 / g.

2. The modified TiO2 / g-C3N4 photocatalyst according to claim 1, characterized in that: The mass ratio of the TiO2 / g-C3N4 to the nano-carbon hydrogen white mud is 1 to 9:

1.

3. The modified TiO2 / g-C3N4 photocatalyst according to claim 1 or 2, characterized in that: The average particle size of the modified TiO2 / g-C3N4 photocatalyst is 20-30 μm, and / or the porosity of the nanocarbon white mud is 65-85%, and / or the average particle size of the nanocarbon white mud is 2.2-13.5 μm, and / or the specific surface area of ​​the nanocarbon white mud is 70-90 m 2 / g.

4. A method for preparing the modified TiO2 / g-C3N4 photocatalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Step S1, performing a first mixing of raw materials including a titanium source, urea and a solvent A to obtain a first mixture; Step S2, sequentially performing a second mixing and standing of the raw materials including the first mixture, water and the acidic solution to obtain a sol; Step S3, sequentially performing a first drying and a first calcination on the sol to obtain a TiO2 / g-C3N4 precursor; Step S4, subjecting the raw materials including the TiO2 / g-C3N4 precursor, nanocarbon white mud and solvent B to ultrasonic dispersion, first stirring, second drying and second calcination in sequence to obtain the modified TiO2 / g-C3N4 photocatalyst.

5. The preparation method according to claim 4, characterized in that: The step S1 comprises: Mixing the titanium source and the solvent A to obtain a mixed solution; Mixing the mixed liquid with the urea to obtain the first mixture; And / or, the titanium source is tetrabutyl titanate, and / or, the volume ratio of the titanium source to the solvent A is 1:2-3; the mass of the urea and the volume ratio of the tetrabutyl titanate are 0.23-0.46 g / mL; and / or, the solvent A is anhydrous ethanol and / or methanol.

6. The preparation method according to claim 4 or 5, characterized in that: In the step S1, a second stirring is performed during the first mixing process, the second stirring time is 10 to 30 minutes, and / or the second stirring speed is 30 to 60 rpm, and / or the second stirring temperature is 20 to 30°C.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In the step S2, the volume ratio of the acidic solution to the water is 1:10 to 1:14; and / or the acidic solution is selected from hydrochloric acid and / or acetic acid with a molar concentration of 10 to 12 mol / L; and / or the water is deionized water; And / or, a third stirring is performed during the second mixing process, the third stirring time is 30 to 60 minutes, and / or, the third stirring speed is 30 to 60 rpm, and / or, the third stirring temperature is 20 to 30° C.; and / or, the standing time is 12 to 24 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In the step S3, the temperature of the first drying is 80-95°C, and / or the time of the first drying is 4-8h; and / or the first calcination is performed at a heating rate of 5-8°C / min and then cooled to room temperature, and / or the temperature of the first calcination is 500-600°C, and / or the time of the first calcination is 2-5h.

9. The preparation method according to any one of claims 4 to 8, characterized in that: In the step S4, the mass ratio of the TiO2 / g-C3N4 precursor to the nanocarbon white mud is 1.5-3.96:1; and / or, the mass ratio of the TiO2 / g-C3N4 precursor to the volume ratio of the solvent B is 0.028-0.084 g / mL; and / or, the solvent B is anhydrous ethanol and / or methanol; and / or, the nanocarbon white mud is obtained by acid dissolution of nanocarbon fly ash.

10. The preparation method according to any one of claims 4 to 9, characterized in that: In the step S4, the ultrasonic dispersion time is 30 to 60 minutes; and / or the ultrasonic dispersion frequency is 20 to 50 kHz; and / or the first stirring time is 4 to 6 hours, and / or the first stirring speed is 40 to 80 rpm, and / or the first stirring temperature is 20 to 30°C; And / or, the temperature of the second drying is 80-95°C, and / or, the time of the second drying is 2-6h; and / or, the second calcination is performed at a heating rate of 5-8°C / min and then cooled to room temperature, and / or, the temperature of the second calcination is 350-450°C, and / or, the time of the second calcination is 2-4h.